Nietzsche on tragedy - Silk, Michael Stephen, 1941-; Stern, Joseph Peter, 1920-1991 (Cambridage : Cambridage university press, 1984)
This is the first comprehensive study of Nietzsche's earliest (and extraordinary) book, The Birth of Tragedy (1872). When he wrote it, Nietzsche was a Greek scholar, a friend and champion of Wagner, and a philosopher in the making. His book has been very influential and widely read, but has always posed great difficulties for readers because of the particular way Nietzsche brings his ancient and modern interests together. The proper appreciation of such a work requires access to ideas that cross the boundaries of conventional specialisms. This is now provided by M. S. Silk and J. P. Stern in their joint study of Nietzsche's book. They examine in detail its content, style and form; its strange genesis and hybrid status; its biographical background and the controversy engendered by its publication; its value as an account of ancient Greek culture and as a theory of tragedy and music; its relation to other theories of tragedy; and its place in the history of German ideas and in Nietzsche's own philosophical career.
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Greek drama (Tragedy) -- History and criticism; Music -- Philosophy and aesthetics; Tragedy; Tragic, The